An epidemic investigation of hepatitis E in Juna Sachivalay area of Gandhinagar city, Gujarat, India - Verma, P. B.; Thakor, Nilesh; Goswami, Mihir (International Journal Of Community Medicine And Public Health, 2016)
Background: Hepatitis E occurs around the world both as outbreaks and as sporadic cases. The objectives of the study were, to perform a detailed epidemiological investigation of an outbreak to determine the incidence of the disease, cause and source of the outbreak and to propose appropriate control and preventive measures. Methods: An outbreak of jaundice had been reported from Juna Sachivalay area of Gandhinagar city to Gandhinagar Municipal Corporation during mid January 2016. Epidemic investigation was started by Rapid Response Team of GMERS Medical College, Gandhinagar in all blocks of Juna Sachivalay during 03/02/2016 to 03/03/2016. Total 4395 employees were surveyed and line listing of cases had been made. Water sample had been also collected from suspected 9 places to examine contamination and chlorination. Plasma samples from randomly selected 16 patients were screened for anti-HEV and HEA IgM antibodies using ELISA to confirm the diagnosis. Results: Total 4395 employees were surveyed. Out of 4395 employees, 124 have a recent history of jaundice. Attack rate of Hepatitis E in our study was 2.82%. Out of these cases, 92 cases were contacted either by personal interview or telephonic interview. 16 patients were screened for anti-HEV and HEA IgM antibodies using ELISA to confirm the diagnosis and found positive for Hepatitis E. So, epidemic of Hepatitis E was confirmed. Age range of the patients was 20 years – 65 years. Out of 92 cases, majority (77, 83.7%) were male. Majority of the cases, (62 cases, 67.39%) were reported between 21-50 years age group. (Table 1) Water samples were collected from suspected 9 places to examine chlorination and contamination. Conclusions: Water sources of 1st and 2nd floor Block-11, Block-12, 1st floor Block-1, in front Gujarat board office and Meenabazar, area nearby Sachivalay was found polluted and contaminated with fecal matter, human excreta or sewage was the reason of an epidemic of Hepatitis E.